Influence of Anthropogenic Pressures on the Bioactivity Potential of Sponges and Soft Corals in the Coral Reef Environment - Hedi Indra Januar; Ekowati Chasanah; Dianne M. Tapiolas; Cherie A. Motti; Catherine H. Liptrot; Anthony D. Wright (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2015)
The wealth of marine sponges and soft corals in Indonesian waters represents a rich source of natural products. However, anthropogenic pressures potentially decrease diversity in coral reefs. Presented here are trends for tropical sponge and soft coral biodiversity and their bioactivity potential under the influence of increasing anthropogenic pressures. Samples were collected along transects (near, mid, and far) at Karimunjawa and Seribu Islands Marine National Parks and environmental parameters (salinity, pH, dissolved oxygen (DO), phosphate, nitrate, and ammonia), sponge and soft coral biodiversity, and the bioactivity potential of those organisms (50% Growth Inhibition (GI50) of cancer cell lines H460-Lung, MCF7-Breast, and SF268-CNS) are compared. The environmental conditions and biodiversity were found to be significantly different between groups of sampling sites (P0.05). Canonical Discriminant Analysis (CDA) revealed DO was the discriminant factor driving the separation between groups (90.1%). Diversity tended to be higher in the Far group with strong and significant relation to DO (R= 0.611, P0.05) and ammonia (R = -0.812, P0.05). The CDA also showed that an increase in bioactivity (low % GI50) of sponge and soft coral extracts was related to a canonical function (57.21%) consisting of high DO, high pH, and low nutrients. These findings indicate the production of bioactive compounds is related to diversity and complexity of coral reef systems. Therefore, strategies for marine protection by mitigating the impacts of anthropogenic pressures needs to be optimized in order to conserve the overall environment and sustain its natural bioactivity potential indefinitely.